Land Suitability Analysis for Land Spinach Plants Using Geographic Information Systems (GIS) in Poka Village, Ambon City - Buatan, Ahmad; Salakory, Melianus; Riry, Roberth Berthy (Program Studi Pendidikan Geografi FKIP Universitas Pattimura, 2023)
Land evaluation is used as a strategic planning tool. Therefore, it must be classified based on capability and suitability classes. The land of Poka Village has been utilized for agricultural activities without considering the suitability class, so the results have yet to be maximized. Evaluation is needed. This study aims to determine the condition of land suitability for cultivating land spinach (ipomoea pair) in Poka Village and to determine the proper recommendations in land management for cultivating land spinach in Poka Village based on land suitability studies. The method used is a field observation survey. The distance of the observation point is 20 m per 1 bed. The study results showed that two land suitability classes were limiting factors: Base Saturation (KB) and C-Organic (Marginal Suitability S3). Efforts to overcome this problem are made through moderate management levels, including liming or adding organic materials such as compost or green manure.